Exploring the role of community pharmacists in addressing obesity: a Saudi Arabian perspective - AlOmeir, Othman; Almuqbil, Mansour; Alhabshi, Hanaa Ali; Alenazy, Maha Mahrab Saiel; Masaod Hagwi, Saleha Mafareh Al-Jaro; Alsanie, Walaa F.; Alamri, Abdulhakeem S.; Alhomrani, Majid; Alshammary, Amal F.; Gilkaramenthi, Rafiulla; Asdaq, Syed Mohammed Basheeruddin (Frontiers in Public Health, 2025)
IntroductionObesity has emerged as a significant public health concern in Saudi Arabia, with rising prevalence rates contributing to an increased risk of chronic diseases such as diabetes and cardiovascular disorders. Community pharmacists, as accessible healthcare providers, hold the potential to play a critical role in weight management. This study aimed to explore the beliefs, practices, and barriers encountered by community pharmacists in Saudi Arabia regarding weight management.MethodsA cross-sectional survey was conducted among community pharmacists to gather data on their perceptions, practices, and barriers related to obesity management. The data obtained were subjected to descriptive and inferential analysis using a multinomial regression model with the help of SPSS-IBM 2025.ResultsFindings revealed that while a significant majority (73%) recognize obesity as a pressing health issue, only 31% reported receiving formal education on weight management, which impedes their ability to provide effective counseling. The demographic profile of respondents showed a predominance of male pharmacists (91%) aged between 31 and 40 years, which reflects broader societal trends in healthcare professions in the region. Furthermore, barriers such as inadequate staffing (39%), lack of private consultation spaces (37%), and the necessity for additional payment for weight management services (49%) were identified, underscoring the need for targeted support. Pharmacists showed a strong dedication to helping patients adopt healthier lifestyles. Specifically, 76% of pharmacists provided advice on following low-calorie diets, and 83% encouraged patients to increase their physical activity. However, only 33% regularly dispensed weight loss products, indicating a gap in practice.DiscussionEnhanced education and supportive policies are crucial for pharmacists in obesity management. Future research should focus on developing tailored training programs to fill the knowledge gaps and explore financial incentives to optimize pharmacists’ roles in public health initiatives aimed at combating obesity and chronic diseases in Saudi Arabia. By addressing these barriers, community pharmacists can significantly contribute to obesity management and improve health outcomes in their communities.